Main Problems in the Activity of the Transport System of Nukus and Kungirot City (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article covers the importance of planning the cargo and passenger transport system of the region in terms of the functional planning of the transport system in cities.